2012
DOI: 10.3390/metabo2010100
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Polyketide Metabolism in Aspergillus nidulans

Abstract: Secondary metabolites are small molecules that show large structural diversity and a broad range of bioactivities. Some metabolites are attractive as drugs or pigments while others act as harmful mycotoxins. Filamentous fungi have the capacity to produce a wide array of secondary metabolites including polyketides. The majority of genes required for production of these metabolites are mostly organized in gene clusters, which often are silent or barely expressed under laboratory conditions, making discovery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 122 publications
(257 reference statements)
1
33
0
Order By: Relevance
“…It was also suggested that different prenyltransferases are responsible for the formation of prenylated benzophenones and xanthones in a given strain. [25] Isolation of preshamixanthone from A. nidulans A4 strongly supports this hypothesis. [24] Seven putative genes encoding members of the DMATS superfamily were identified in the genome of A. nidulans A4.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…It was also suggested that different prenyltransferases are responsible for the formation of prenylated benzophenones and xanthones in a given strain. [25] Isolation of preshamixanthone from A. nidulans A4 strongly supports this hypothesis. [24] Seven putative genes encoding members of the DMATS superfamily were identified in the genome of A. nidulans A4.…”
Section: Discussionmentioning
confidence: 71%
“…12, 24 It would be therefore interesting to investigate the substrate specificity of XptB orthologues from some producers of prenylated benzophenones. It was also suggested that different prenyltransferases are responsible for the formation of prenylated benzophenones and xanthones in a given strain 25. Isolation of pre‐shamixanthone from A. nidulans A4 strongly supports this hypothesis 24.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Going in line with this, lack of cclA resulted in the induction of monodictyphenone/emodin and the two antiosteoporosis polyketides F9775A and F9775B in A. nidulans , increased gliotoxin production in A. fumigatus as well as induction of the sesquiterpenoid astellolides in A. oryzae (Bok et al, 2009; Palmer et al, 2013; Shinohara et al, 2016). Strikingly, both non-reducing PKS-encoding genes, mpdG (AN0150) and orsA (AN7909), involved in the biosynthesis of monodictyphenone/emodin and F9775A/F9775B, respectively, are localized in subtelomeric regions in A. nidulans (Klejnstrup et al, 2012). Notably, lack of the KDM5-family histone demethylase KdmB, involved in the removal of H3K4 di- and trimethylation marks, showed an identical phenotype concerning these two polyketides (Gacek-Matthews et al, 2016), suggesting that KdmB targeting H3K4 methylation plays a role in negative regulation of these clusters in some way.…”
Section: Discussionmentioning
confidence: 99%
“…We also describe the current status of the annotation of the products of secondary metabolism genes in A. nidulans . We would also like to direct readers to the accompanying review in this issue by our collaborators Nancy Keller and Philipp Wiemann on general strategies for mining fungal natural products and to other recent reviews on this subject [10, 28, 53, 56, 61]. …”
Section: Introductionmentioning
confidence: 99%